Carbon footprint of biodiesel production using waste cooking oil: Performance and analysis through amberlite HPR 9000 SO4 as catalyst - Anggara Dwita Burmana; Renita Manurung; Affila; Aga Nugraha; Asri Munawar; Rondang Tambun (Results in Engineering)
This study presents Amberlite HPR 9000 SO4, a strong base anion exchange resin uniquely engineered with a uniform particle size and macro porous structure, delivering exceptional resistance to surface fouling and operational stresses. Unlike conventional resins, Amberlite HPR 9000 SO4 demonstrates enhanced resin lifetime and reliable performance. This study aims to determine the effectiveness of the Amberlite HPR 9000 SO4 catalyst in the biodiesel production process by studying at the reaction conversion and flash point achieved and measuring the carbon footprint generated from this process. The amount of catalyst used in the transesterification reaction plays an important role in the conversion of oil or fat into biodiesel. In this study, the best amount of catalyst was 20% at 300 rpm and 65 °C with a conversion value of 79.8%. The flash point of biodiesel has a significant impact on its storage and handling as it affects safety and regulatory compliance. The flash point of biodiesel can also be affected by the level of methanol in the biodiesel during the production process. The highest flash point obtained in this study was 171.5 °C with a 5% acid treatment, 20% catalyst and a stirring speed of 400 rpm. This study's comparative analysis of emissions shows that biodiesel produces lower emissions than petrodiesel. The global warming potential of biodiesel produced with the HPR 9000 SO4 catalyst is 0.0031 kg CO2 eq. Meanwhile, the acidification and eutrophication potentials are 0.0065 kg SO2 eq and 0.0003 kg PO4 eq, respectively. The catalyst's reusability was confirmed for seven cycles without additional treatment.